ON HEALTH PROTECTION AND HEALTH RELATED PHYSICAL CULTURE TRAININGS OF FIRST YEAR STUDENTS - V.G. Fotynyuk (Physical Education of Students)
Purpose: to assess health protection and health related physical culture trainings of first year students. Material: in the research first year students (n=121; 86 boys and 35girls of age 16 - 19 years, participated. Results: components of students’ individual health were found. Situation with health related physical culture trainings, ensuring students’ sound health and optimal functional potentials of their organisms were determined. It was found that leading role shall be played by formation of health world vision values, knowledge about formation of practical skills in healthy life style. Motivation tendency for realization of intentions and practicing of health related physical culture trainings were found in students. Conclusions: the received results prove students’ tendency to pay insufficient attention to individual health. It was found that health related physical culture trainings require modern renewal of education’s content, forms and methods of physical education. The basis of such trainings shall be health related orientation.